Metal specific partitioning in a parasite–host assemblage of the cestode Ligula intestinalis and the cyprinid fish Rastrineobola argentea - Oyoo-Okoth, Elijah; Admiraal, Wim; Osano, Odipo; Hoitinga, Leo; Kraak, Michiel H.S. (The Science of the total environment, 2010)
When evaluating metal accumulation patterns in parasite–host assemblages species specific metal requirements should be taken into account. The aim of the present study was therefore to determine the metal specific partitioning in a parasite–host assemblage of the cestode Ligula intestinalis and the cyprinid fish Rastrineobola argentea and to determine the effect of the parasites on the metal balance of the fish. To this purpose the host–parasite assemblage was analysed for several metals at sites in the coastal zone of Lake Victoria differing in metal contamination. Our results showed that some elements (Ca, Sr, and Mg) reflected the physiological differences of bone formation and ionic balance and pointed to physiological disturbances of infested R. argentea. Other essential metals including Cu and Co were subject of element competition between fish and parasite, while only a micro-element (Cr) and a non-essential metal (Cd) displayed a partitioning with high concentration in the parasite. The present study clearly demonstrated the impact of the large cestodes on their small fish hosts and it is concluded that the partitioning of metals in the assemblage of R. argentea and L. intestinalis is subject to metal specific mechanisms for essential and non-essential elements.